Marginalized Bodies of Imagined Futurescapes : Ableism and Heteronormativity in Science Fiction - Wälivaara, Josefine (My University, 2018)
This article aims to contribute to an understanding of marginalized bodies in science fiction narratives by analyzing how physical disability and homosexuality/bisexuality have been depicted in popular science fiction film and television. Specifically, it analyzes what types of futures are evoked through the exclusion or inclusion of disability and homo/bisexuality. To investigate these futurescapes, in for example Star Trek and The Handmaid’s Tale, the paper uses film analysis guided by the theoretical approach of crip/queer temporality mainly in dialogue with disability/crip scholar Alison Kafer. Although narratives about the future in popular fiction occasionally imagines futures in which disability and homo/bisexuality exist the vast majority do not. This article argues that exclusion of characters with disabilities and homo/bisexual characters in imagined futures of science fiction perpetuate heteronormative and ableist normativity. It is important that fictional narratives of imagined futures do not limit portrayals to heterosexual and able-bodied people but, instead, take into account the ableist and heteronormative imaginaries that these narratives, and in extension contemporary society, are embedded in. Moreover, it is argued that in relation to notions of progression and social inclusion in imagined futurescapes portrayals of homo/bisexuality and disability has been used as narrative devices to emphasis “good” or “bad” futures. Furthermore, homo/bisexuality has increasingly been incorporated as a sign of social inclusion and progression while disability, partly due to the perseverance of a medical understanding of disability, instead is used as a sign of a failed future. However, the symbolic value ascribed to these bodies in stories are based on contemporary views and can thus change accordingly. To change the way the future is envisioned requires challenging how different types of bodies, desires, and notions of normativity are thought about. Sometimes imaginary futures can aid in rethinking and revaluating these taken-for-granted notions of normativity.
Keywords: 306 Kultur und Institutionen; future; science fiction; disability; queer; temporality